Two new species of Onciderini Thomson, 1860 (Cerambycidae: Lamiinae) from Mexico and Honduras - Pérez-Flores, Oscar; Nearns, Eugenio H. (Zootaxa, 2021)
Hesychotypa albofasciata sp. nov. from Mexico (Veracruz) and Honduras, and Tulcus santossilvai sp. nov. from Mexico (Oaxaca) are described and illustrated. Distinguishing characters from closely related species are provided and discussed.